A survey of the current industrial pollution problems : A perspective for chemical engineers - Taib, Mohamad Rozainee (1990)
A survey on the current and the anticipated pollution problems in various industries in West Malaysia was carried out recently. About 60 percent out of the 113 industries investigated are facing various pollution problems. The main types of the problem in descending scale include air (21.4%), noise (19.8%), water (18.3%), solid wastes (18.3%), and toxic and hazardous waste (12.0%). The study indicated that Chemical Engineers, to a greter extent, can play an important role in solving the multitude local industrial pollution problems. In developed countries such as the United States of America with a marked concern for environmental protectionism, the industrial related pollution problems are often tackled by Chemical Engineers. This is because the Chemical Engineers have a sound knowledge on the industrial processes which can further enable them to minimize the generation of pollutants from industries, and also to treat and dispose of such pollutants securely. Details of the survey and the possible future roles of Chemical Engineers in solving such problems are highlighted further in this paper.